EFEK TERAPI PURIFIED PROTEIN DERIVATIVE TERHADAP KADAR INTERLEUKIN-12 SERUM PASIEN KUTIL ANOGENITAL (Media Dermato Venereologica Indonesiana, 2022)
Anogenital warts (AGWs) are benign epithelial proliferation of the skin/mucosa, caused by human papillomavirus (HPV), with clinical manifestation of warts in the genital/perianal areas. Cellular immunity plays a role in the elimination of HPV, which characterized by the expression of cytokines with Thelper (Th)-1 cell pattern, namely interleukin (IL)-12 which will increases Tcell proliferation and differentiation into Th-1, pro-inflammatory cytokines secretion, also induce natural killer cells to increase proliferation and pro-inflammatory cytokines. In in vitro studies, PPD increased IL-12 expression in serum verruca vulgaris patients (p<0,05) compared to control. There are no study of serum IL-12 levels in AGWs petients who received intralesional PPD injection in Indonesia, so this is the aim of this study. This research isone group pre- and post-test design based on an experimental analytic study. The samples were 14 serum of AGWs patients before and after receiving PPD therapy. Serum IL-12 levels meassured by enzyme linked immunosorbent assay. Results showedserum IL-12 levels before receiving therapy was 45.73±53.186pg/ml. After receiving PPD therapy, serum IL-12 levels increased by an average of 45.9pg/ml, became 91.68±79.321pg/ml (p=0,158). As conclusion,level of IL-12 in the serum of AGWs patients does not increase after receiving PPD therapy.